Money - L. Randall Wray (Levy Economics Institute of Bard College, 2010)
This paper advances three fundamental propositions regarding money: (1) As R. W. Clower (1965) famously put it, money buys goods and goods buy money, but goods do not buy goods. (2) Money is always debt; it cannot be a commodity from the first proposition because, if it were, that would mean that a particular good is buying goods.(3) Default on debt is possible. These three propositions are used to build a theory of money that is linked to common themes in the heterodox literature on money. The approach taken here is integrated with Hyman Minsky's (1986) work (which relies heavily on the work of his dissertation adviser, Joseph Schumpeter [1934]); the endogenous money approach of Basil Moore; the French-Italian circuit approach; Paul Davidson's (1978) interpretation of John Maynard Keynes, which relies on uncertainty; Wynne Godley's approach, which relies on accounting identities; the K distribution theory of Keynes, Michal Kalecki, Nicholas Kaldor, and Kenneth Boulding; the sociological approach of Ingham; and the chartalist, or state money, approach (A. M. Innes, G. F. Knapp, and Charles Goodhart). Hence, this paper takes a somewhat different route to develop the more typical heterodox conclusions about money.
Keywords: E4; E5; E6; E11; E12; B5; B15; B22; 330; money; credit; debt; uncertainty; default; unit of account; heterodox; circuit approach; Godley; Minsky; Knapp; Schumpeter; endogenous money; Geldtheorie; Dogmengeschichte; Theorie